Assessment of Digital Literacy Skills and Exploitation of Electronic Resources by Undergraduate Students in Tertiary Institutions in Akwa Ibom State, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2025)
The work accessed digital literacy skills and exploitation of electronic resources by Undergraduate Students in tertiary institutions in Akwa Ibom State. The main objective was to evaluate students’ digital skills in utilization of electronic resources. The study was conducted in three tertiary institutions in the study area. The population of the study was 1,570 registered undergraduate students for the 2022/2023 academic session, out of which a sample size of 375 were selected through accidental sampling techniques to take part in the study. The instrument for data collection was a questionnaire titled, "Digital Literacy Skills and Exploitation of Electronic Resources by Undergraduate Students in tertiary institutions Questionnaire (DLSEERUEQ). The instrument was validated by two experts in University of Uyo, one of whom is an expert in the education foundation test and measurement from the University of Uyo. The data collected was analyzed using simple regression analysis in answering both research questions and testing of hypotheses at .05 level of significance. The results revealed that there is significant relationship between digital literacy skills and exploitation of electronic resources by Undergraduate Students in tertiary institutions in Akwa Ibom State. The study conclude that the digital skills is an essential skill for effective utilization of electronic resources in today global environment. Hence, recommends among that Departments in tertiary institutions should be collaborate to design course contents on analytical skills in order to help students acquire analytical skills in accessing information as well as data interpretation.Keywords: digital skills, exploitation